1969
DOI: 10.1037/h0027070
|View full text |Cite
|
Sign up to set email alerts
|

Oral imagery and alcoholism.

Abstract: Twenty Veterans Administration patients with histories of heavy daily alcoholic consumption were matched on age, education, IQ, and diagnosis with 20 patients with no history of reliance on alcohol, and then-scores on a Rorschach measure of orality were compared. As predicted, the alcoholics gave more oral dependent responses than the controls (p = .01). Although total scores on oral sadism did not discriminate between groups, the alcoholic 5s gave more responses on two of the oral sadistic subcategories, burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The present findings agree with previous research into the relationship between orality and certain other psychopathologies: for example, alcoholism (Bertrand & Masling, 1969;Weiss & Masling, 1970), obesity (Masling et al 1967;Weiss & Masling, 1970), schizophrenia (Lewis, Griffith, Riedel, & Simmons, 1959), and stuttering (Weiss & Masling, 1970). And in clinically depressed samples, a number of researchers have found increased levels of symbolic oral-dependent behaviors such as smoking and asking to be physically held and comforted (for example, Blatt, Quinlan, Chevrons, Mc-…”
Section: Discussionsupporting
confidence: 91%
“…The present findings agree with previous research into the relationship between orality and certain other psychopathologies: for example, alcoholism (Bertrand & Masling, 1969;Weiss & Masling, 1970), obesity (Masling et al 1967;Weiss & Masling, 1970), schizophrenia (Lewis, Griffith, Riedel, & Simmons, 1959), and stuttering (Weiss & Masling, 1970). And in clinically depressed samples, a number of researchers have found increased levels of symbolic oral-dependent behaviors such as smoking and asking to be physically held and comforted (for example, Blatt, Quinlan, Chevrons, Mc-…”
Section: Discussionsupporting
confidence: 91%
“…As reviewed by Bornstein (1996a), the ROD has significantly predicted relevant behavioral criteria including help seeking (Shilkret & Masling, 1981), compliance (Bornstein & Masling, 1985), and sensitivity to interpersonal cues (Masling, Johnson, & Saturansky, 1974). ROD scores have been linked to relevant types of psychopathology such as depression (O'Neill & Bornstein, 1991) and alcoholism (Bertrand & Masling, 1969). It is worth noting that the most vocal Rorschach critics have written favorably about the properties of the ROD and the research programs that have examined it (Garb, Wood, Lilienfeld, & Nezworski, 2005;Hunsley & Bailey, 2001).…”
Section: Assessment Of Interpersonal Dependencymentioning
confidence: 98%
“…The scoring for oral and dependent responses was actuarial and mechanical, using a lexical approach; specific words and themes were scored, regardless of context, affect, or appropriateness or quality of the response. Although such characteristics of a response are extremely important in any clinical assessment of a single person, previous research using our lexical system (Bertrand & Masling, 1969;Juni et al, 1979;Masling et al, 1974;Masling, Rabie, & Blondheim, 1967;Masling et al, 1980;Masling et al, 1968) has amply demonstrated the utility of this actuarial method in discriminating between groups; the concept of orality is evidently sufficiently robust to withstand the loss of such clinically useful data. Since previous research has established an interscorer reliability on this dimension of 89% to 96% with a rank-order correlation between raters of .91 (Juni et al, 1979), only one rater was used.…”
Section: Subjectsmentioning
confidence: 99%